2018
DOI: 10.1097/md.0000000000010930
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-related difference of lipid profile in patients with ischemic stroke in China

Abstract: Age- and sex-related differences of lipid profiles were not well understood among ischemic stroke patients in China. Our study aimed to investigate the relationship between lipid abnormalities and ischemic stroke in China. A retrospective analysis was performed involving 2074 patients with ischemic stroke who admitted to Meizhou People's Hospital (Huangtang Hospital), Meizhou Hospital Affiliated to Sun Yat-sen University between January 1, 2014 and March 1, 2017. Our study indicated that there were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
14
2
Order By: Relevance
“…Our results showed that, there was no significant difference in lipid profile variable between two age groups (younger and older adult). Our results are incontinent with Manjareeka et al [11] and Zhao et al [33]. The contradiction in our findings with other studies is probably due to:(1) the small sample size compared to other studies, (2) most of the subjects who participated in this study, were nearly 40 years old (men40±7, women39±5).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that, there was no significant difference in lipid profile variable between two age groups (younger and older adult). Our results are incontinent with Manjareeka et al [11] and Zhao et al [33]. The contradiction in our findings with other studies is probably due to:(1) the small sample size compared to other studies, (2) most of the subjects who participated in this study, were nearly 40 years old (men40±7, women39±5).…”
Section: Discussioncontrasting
confidence: 91%
“…On the other hand, our results showed that, there was a significant difference in anthropometric indices between two age groups (younger and older adults). Our results are supported by Manjareeka et al [11] and Zhao et al [33]. The difference in anthropometric indices between two age groups is probably due to the fat mass increment related to aging.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to study by Zhao et al, (2018) in which lipid abnormality was more prevalent in nonelderly patients (74% vs. 67%, P<0.05). 9 The proportion of double-abnormality in nonelderly patients was significantly higher than that in elderly patients (27% vs. 21%, P<0.05), whereas no difference was seen. The copper levels were higher in controls, showing imbalance in their levels.…”
Section: Resultsmentioning
confidence: 77%
“…Similar to the study that of Zhao et al, in which lipid abnormality was more prevalent in nonelderly patients (74% vs. 67%, P<0.05). 12 The proportion of double-abnormality in nonelderly patients was significantly higher than that in elderly patients (27% vs. 21%, P<0.05), whereas no difference was seen. When vitamin C levels were compared between males and females, males had non-significant difference than females (Table 3).…”
Section: Discussionmentioning
confidence: 77%